SINTESIS (E)-3-(3-BROMOFENIL)-1-(NAFTALEN-2-IL)PROP-2-EN-2-ON DARI 2-ASETILNAFTALEN DAN 3-BROMOBENZALDEHID - I. Muttakin; N. Balatif; Jasril ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Chalcone of (E)-3-(3-bromophenil)-1-(naphtalen-2-yl)prop-2-en-2-one has beensynthesized from 2- acethylnapthalene and 3- bromobenzaldehyd by aldol condensationusing the stirring method with base catalyst (NaOH). The yield obtained for thiscompound was 61.21 %. The purity of product has been evaluated using TLC, meltingpoint test, and HPLC analysis. The structure of the synthesized compound wasconfirmed by UV UV, FTIR, NMR, and MS analysis. Data characterization showed thatthe compound obtained was the targeted compound.